2003
DOI: 10.1159/000073762
|View full text |Cite
|
Sign up to set email alerts
|

Numbers of Neurons in the Retinal Ganglion Cell Layer of the Rat Do Not Change throughout Life

Abstract: Background: There have been many assumptions made about neuronal loss in mammals due to aging. However, when we examined the retinal ganglion cell layer of a marsupial, the quokka, from 0.5 to 13.5 years of age, we found that the total neuron number did not decrease significantly even into extreme old age. The retinal area increased slowly throughout life, leading to a decrease in cell density. Neuronal death in the rat retina has been assumed, since the cell density has been seen to fall with age. However, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…Our results are consistent with those studies in which the total number of retinal ganglion cells was estimated Kim et al, 1996;Harman & Moore, 1999;Harman et al, 2003! but against other studies in which the cell density~per unit area! Our results are consistent with those studies in which the total number of retinal ganglion cells was estimated Kim et al, 1996;Harman & Moore, 1999;Harman et al, 2003! but against other studies in which the cell density~per unit area!…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with those studies in which the total number of retinal ganglion cells was estimated Kim et al, 1996;Harman & Moore, 1999;Harman et al, 2003! but against other studies in which the cell density~per unit area! Our results are consistent with those studies in which the total number of retinal ganglion cells was estimated Kim et al, 1996;Harman & Moore, 1999;Harman et al, 2003! but against other studies in which the cell density~per unit area!…”
Section: Discussionsupporting
confidence: 93%
“…was used for comparisons between age groups~Cano et al, 1986; Gao & Hollyfield, 1992;Weisse, 1995;Cavallotti et al, 2001!. and previous studies Cano et al, 1986;Weisse, 1995;Cavallotti et al, 2001;Harman et al, 2003! proved that the thickness of the retina significantly decreased whereas the area of the entire retina increased during the aging process. Evidence from this study~Table 1!…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that astrocytes lose their ability to proliferate after 9 months, equivalent to a young adult in humans, and that the frequency of apoptosis increases significantly and persistently into old age [21]. In contrast, retinal ganglion cell numbers have been shown to remain constant in the rat retina with age [22]. Thus during aging a lower astrocyte to neuronal ratio results, placing an increased demand on the remaining astrocytes to maintain retinal homeostasis [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the widespread use of the rat in retinal research, there are only a few studies of retinal age-related molecular and morphological changes covering the first 6 months of life. Although a few histological analyses of the rat retina were reported, including a morphometric study in the first 2 weeks of life [11] and RGC count in 3 and 6 month-old rats [12], we are aware of only one study in which a sequential analysis of the rat retina between weaning and adulthood was performed [13].…”
Section: Introductionmentioning
confidence: 99%